Brush‐First Synthesis of Core‐Photodegradable Miktoarm Star Polymers via ROMP: Towards Photoresponsive Self‐Assemblies. Issue 2 (22nd November 2013) - Burts, Alan O.; Gao, Angela X.; Johnson, Jeremiah A.; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> This report describes the synthesis of miktoarm brush‐arm star polymers (BASPs) from branched and linear norbornene‐terminated macromonomers (MMs) via the brush‐first ring‐opening metathesis polymerization (ROMP) method. First, a polystyrene (PS)‐branch‐poly(lactic acid) (PLA) MM is synthesized via a combination of atom transfer radical polymerization (ATRP), tin(II)‐mediated ring opening polymerization, and copper‐catalyzed azide‐alkyne cycloaddition reactions. Graft‐through ROMP of this MM followed by in situ cross‐linking with a photo‐cleavable bis‐norbornene derivative provided nanoscopic BASPs with photodegradable cores and a precise 1:1 PS:PLA arm composition. Three‐miktoarm BASPs are prepared in an analogous manner via copolymerization of the same PS‐branch‐PLA MM with a poly(ethylene glycol) (PEG) MM prior to cross‐linking. Intramolecular phase segregation of these miktoarm BASPs is characterized by transmission electron microscopy (TEM); a UV‐induced structural rearrangement from three‐faced Janus particles to micelles is observed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>